Genre, language and strategies of today´s advertising discourse - Carvalho, Cristiane Mafacioli (2013)
This article presents an overview about the concepts of social discourses, mainly stemming from Eliseo Verón and Patrick Charaudeau, and applies them to the advertising genre, aiming to raise issues that could feed the studies that concern the field. The article looks to align references treated with the moment that current advertising is presented, processing and changing practices and languages. In order to illustrate these changes the article presents, at the end of the study, a description of a program developed by the brand Olympikus, seeking to identify the strategies employed by this new type of advertising discourse.